2015
DOI: 10.14814/phy2.12641
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to bladder inflammation in smokers: targeting the PAF-PAF receptor interaction to manage inflammatory cell recruitment

Abstract: Chronic bladder inflammation can result in a significant reduction in quality of life. Smoking remains a leading preventable risk factor in many diseases. Despite the large amount of evidence supporting the risks of smoking, roughly 45 million people in the United States remain smokers. The impact of cigarette smoking on inflammation is well established, but how smoking promotes bladder inflammation is currently unknown. The aim of this study was to determine if cigarette smoke exposure impacts inflammatory ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
(60 reference statements)
0
17
0
Order By: Relevance
“…To date, the mechanism underlying cigarette smoke-induced bladder pain has not been elucidated. In a recent study (Marentette et al 2015), we showed that cigarette smoking was associated with increased PAF production and adherence of inflammatory cells to the bladder endothelium. Additionally, mice exposed to cigarette smoking for 4 weeks showed increased accumulation of inflammatory cells in the bladder wall (Marentette et al 2015).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…To date, the mechanism underlying cigarette smoke-induced bladder pain has not been elucidated. In a recent study (Marentette et al 2015), we showed that cigarette smoking was associated with increased PAF production and adherence of inflammatory cells to the bladder endothelium. Additionally, mice exposed to cigarette smoking for 4 weeks showed increased accumulation of inflammatory cells in the bladder wall (Marentette et al 2015).…”
Section: Discussionmentioning
confidence: 89%
“…; Marentette et al. ). However, increased PAF in response to smoking can be inhibited by treatment with inhibitors of iPLA 2 β , the predominant PLA 2 isoform responsible for PAF production in endothelial (McHowat et al.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Histological evaluation of the bladder revealed denudation and thinning of the urothelium, and results from a previous study indicated infiltration of inflammatory cells into the bladder wall (Marentette et al. ), in wild‐type mice but not in iPLA 2 β −/− mice. Interestingly, the expression of PAF and its receptor was elevated in the urothelium of the wild type mice but not of the iPLA 2 β −/− mice exposed to smoke.…”
mentioning
confidence: 84%